The Effect of Cash Holdings on Debt Cost: The Moderating Role of Ownership Structure and Operating Risk in SBF120 French Listed Companies - Chaieb, Souad (New Advances in Business, Management and Economics Vol. 4, 2025)
Purpose: This paper aims to explore the relationship between cash holdings and the cost of debt, while examining the moderating effects of ownership structure and operating risk on this relationship. Design/Methodology/Approach: The study is conducted on a sample of 100 French companies listed on the SBF120 index, covering a five-year period from 2011 to 2015. Quantitative methods are employed to analyze the influence of cash holdings on debt costs, while accounting for the moderating roles of ownership structure and operating risk. Data are drawn from the financial statements and reports of these firms. Findings: The findings reveal a significant and negative effect of cash holdings on the cost of debt. Firms that maintain higher liquidity levels face lower borrowing costs. Additionally, ownership structure and operating risk are found to influence the strength of this relationship. Originality/value: This research provides insights into the financial strategies of French listed companies, emphasizing the importance of liquidity in mitigating borrowing costs. It also sheds light on the roles of ownership structure and risk management in shaping financial outcomes. The study offers practical recommendations for firms seeking to balance cash holdings and financing costs.